On the Hermeneutics of Reading Historical Texts in the Mathematics Classroom - Fossa, John A. (REMATEC, 2021)
A hermeneutical substructure for the reading of historical texts in the mathematics classroom is described. It is organized according to the four transcendentals of unity, truth, beauty and goodness, each of which is considered internally –with respect to the text itself – and externally – with respect to both its relations to mathematical thought in general and other cultural manifestations. Lead questions are provided for each category as are also details regarding various ways in which the student’s interactions with the text can be organized in order to provide the student with a rich learning experience. Some attention is also given to questions relating to implementation.